Pengaruh Aplikasi Vaksin Dan Suplementasi Probiotik Terhadap Titer Antibodi Dan Pertumbuhan Ayam KUB Yang Dipelihara Di Lingkungan Lahan Kering - Sanam, Viona Mariana Dewi; Tangkonda, Elisabet; Sanam, Maxs U.E (Jurnal Veteriner Nusantara, 2024)
The maintenance of chicken livestock is often constrained by several infectious diseases that cause chicken death, one of which is Newcastle Disease. Efficiency in maintaining chicken production can be achieved with probiotics. Probiotic supplementation can reduce the risk of disease and improve chicken health. This study aims to determine the difference in antibody titer of KUB chickens given intramuscular vaccine and drinking water and to know the difference in body weight gain of chickens that get probiotics and those that do not get probiotics. The parameters observed were antibody titer before and after vaccination and body weight gain. This study used the HA and HI test methods. Positive results in the HA test are evenly distributed crystals (diffusion), while negative results in the HA test are flow (tears drop), while the HI test results can be observed by calculating the blood flow that occurs in each well. The results showed that there were significant differences in antibody titers between intramuscular and oral vaccination methods. The provision of probiotics did not show significant differences (P>0.05) on body weight gain of KUB chickens both those who received probiotics and those who did not receive probiotics.